Roles of p53, NF-κB and the androgen receptor in controlling NGAL expression in prostate cancer cell lines. (August 2018) - Chappell, William H.; Candido, Saverio; Abrams, Stephen L.; Russo, Suzanne; Ove, Roger; Martelli, Alberto M.; Cocco, Lucio; Ramazzotti, Giulia; Cervello, Melchiorre; Montalto, Giuseppe; Steelman, Linda S.; Leng, Xiaohong; et al.
Abstract: Neutrophil gelatinase-associated lipocalin (NGAL a.k.a lipocalin 2, lnc2) is a secreted protein which can form a complex with matrix metalloproteinase-9 (MMP9). This MMP9/NGAL complex has been associated with metastasis. MMP9 and NGAL are detected in the urine of patients afflicted with many different types of cancer, including prostate cancer. The effects of p53, NF-κB and the androgen receptor (AR) on the expression of NGAL was examined in four prostate cancer cell lines. Prostate cancer cell lines that are AR negative and expressed either mutant or no p53 (DU145 and PC3) displayed higher levels of NGAL expression compared to the prostate cancer cell lines (LNCaP and 22Rv-1) which are AR positive and express wild type (WT) p53. Introduction of WT-p53 into the PC3 prostate cancer cell line, resulted in reduction of the levels of NGAL expression. Conversely, introduction of dominant negative (DN) p53 or a retroviral construct expressing NF-κB into LNCaP cells increased NGAL expression. NGAL expression had functional effects on the ability of the cells to form colonies in soft agar. Whereas suppression of WT-53 in LNCaP cells increased NGAL expression, the introduction of WT-p53 suppressed NGAL transcription activity in PC3 prostate cells which normally express high level of NGAL. NF-κB and p53 were determined to regulate NGAL expression by positive and negative mechanisms, respectively. Our data indicate that prostate cancer growth, progression and sensitivity to chemotherapeutic drugs are regulated in part by NGAL and may involve complex interactions between NGAL, MMP9, NF-κB and p53.